A CRITICAL REVIEW OF THE ROLE OF COMMERCIAL COURTS IN INDONESIA'S RELIGIOUS JUSTICE SYSTEM - Fauzan Arrasyid (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
The repositioning of jurisdiction for resolving the liquidation of Islamic banks from the Commercial Court to the Religious Court is a crucial issue in the reform of Indonesia’s Islamic economic judicial system. This study aims to identify the inaccuracy of the forum for resolving Islamic bank liquidation cases under the jurisdiction of the Commercial Court. The approach used is normative juridical. The results show that the dominance of the Commercial Court in Islamic bank liquidation cases is contrary to the principle of lex specialis and Constitutional Court Decision No. 93/PUU-X/2012, and ignores the principles of sharia justice. In addition, the non-use of the Kompilasi Hukum Ekonomi Syariah (KHES), the absence of reference to Dewan Syariah Nasional-Majelis Ulama Indonesia fatwas, and the absence of sharia expert witnesses in evidentiary practice, widened the gap between sharia norms and litigation mechanisms. The jurisdictional fragmentation that occurs indicates a systemic failure to integrate the values, procedures and forums of sharia economic law into the national legal system. This research confirms that the repositioning of authority to the Religious Courts needs to be accompanied by cross-regulatory harmonization, strengthening institutional capacity, and affirmation of the constitutional rights of Muslims in choosing religious-based justice forums. This research is expected to be an important contribution to the renewal of a national justice system that is inclusive, responsive and valuable.